Congressional Testimony on the Effectiveness of the Employment Service in Aiding UI Claimants - Louis S. Jacobson (W.E. Upjohn Institute for Employment Research, 1991)
This testimony describes the results of a study of the Employment Service (ES) conducted by Dr. Jacobson and Prof. Arnold Katz of the University of Pittsburgh using data on over 100,000 individuals who registered with the Pennsylvania ES between 1978 and 1987, and an even larger sample of non-registrants. One major finding is that much of the decline in the ES's performance over the past thirty years can be explained by changes in: funding, characteristics of registrants, and characteristics of job vacancies. Thus, we concluded that criticism of the ES often ignores changes in crucial factors outside of the ES's control that reduced its effectiveness. A second major finding is that most criticism of the ES is based on the inappropriate assumption that the primary goal of the ES should be to maximize placements. The proper measure of ES benefits is how well it reduces joblessness, increases earnings, and reduces UI and welfare payments. We found that the ES reduced the average duration of unemployment of long-term UI claimants by nine weeks. This was for UI claimants who were unemployed for at least 30 weeks. But the ES reduced joblessness of claimants unemployed for 12 weeks by less than two weeks. This is evidence that the ES is most effective in aiding claimants who had substantial trouble finding work on their own. But we suspect that the jobs found with the help of the ES do not compare favorably with jobs held prior to becoming unemployed. Thus, we believe the ES primarily acts as a backstop preventing large earnings losses. Finally, although savings in UI benefits and increases in earnings created by the ES may be modest, the cost of ES service is so low, 75 on average, that modest benefits would more than offset those costs. We believe our results, coupled with similar findings from related studies, is sufficiently strong to warrant increasing the funding of the ES. That measure is favored because it would be at least budget neutral. In contrast, other measures to assist the long-term unemployed, such as providing extended UI benefits or training, would not come close to being budget neutral. In addition, 1 spent on job search assistance is likely to be more effective in helping claimants than 1 spent on training.
Keywords: J0; J6; 330; unemployment; insurance; employment; service; displaced; dislocated; Jacobson